1979
DOI: 10.1055/s-0038-1657049
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Cytochalasin B on Platelet Release, Aggregation and Contractility: Evidence against a Contractile Mechanism for the Release of Platelet Granular Contents

Abstract: SummaryCytochalasin B alters the structure and functional properties of filamentous actin. Platelet-mediated clot retraction in dilute platelet-rich plasma (PRP) is inhibited progressively at cytochalasin B concentrations of 0.01 mg/ml, 0.05 mg/ml and 0.1 mg/ml. Dynamic rheological measurements of recalcified PRP in a Weissenberg Rheogoniometer indicate that platelet contractility (as reflected in measurements of elastic moduli) is reduced by 33%, 57% and 63% at cytochalasin B concentrations of 0.01, 0.05 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…Preincubation of platelets with cytochalasin B (20 mM) prevented thrombin-induced actin polymerization but had no effect on platelet aggregation, as earlier reported [Kirkpatrick et al, 1980]. Cytochalasin B treatment completely inhibited the cytoskeletal association of Btk, indicating that actin polymerization is a prerequisite for this process (Fig.…”
Section: The Redistribution Of Btk Is Regulated By Activities Of Protsupporting
confidence: 82%
“…Preincubation of platelets with cytochalasin B (20 mM) prevented thrombin-induced actin polymerization but had no effect on platelet aggregation, as earlier reported [Kirkpatrick et al, 1980]. Cytochalasin B treatment completely inhibited the cytoskeletal association of Btk, indicating that actin polymerization is a prerequisite for this process (Fig.…”
Section: The Redistribution Of Btk Is Regulated By Activities Of Protsupporting
confidence: 82%
“…For example, blocking actin polymerization with cytochalasin enhances the release of plateletdense granules, [33][34][35] suggesting that actin contributes to the regulation of platelet exocytosis, which is analogous to the contribution of actin to neuronal cell exocytosis. 47 Other indications that the cytoskeleton has a role in platelet exocytosis include the observation that preventing myosin light chain phosphorylation impairs platelet secretion 48,49 and that by adding recombinant scinderin (a calcium-dependent F-actin severing protein) to permeabilized platelets enhances dense granule exocytosis.…”
Section: Is the Cytoskeleton The Link Between Pleckstrin And Exocytosis?mentioning
confidence: 99%
“…[33][34][35] Heterologous expression studies show that pleckstrin can reorganize the actin cytoskeleton. 27,28,36 Because the available evidence suggests that disassembly of F-actin facilitates exocytosis in platelets, it is possible that pleckstrin indirectly links PKC with exocytosis by facilitating F-actin reorganization.…”
Section: Pleckstrin and Actin Assemblymentioning
confidence: 99%
“…9 Subsequent studies using similar conditions, however, demonstrated little effect of cytochalasin on collagen-induced dense granule secretion. 10 Studies using other agonists such as thrombin, phorbol esters, calcium ionophore, or adenosine diphosphate (ADP) to study the effect of cytochalasins on dense granule secretion have demonstrated either inhibition or augmentation. [11][12][13] A study evaluating ␣-granule secretion showed no effect of cytochalasin E on thrombin-induced ␣-granule secretion.…”
Section: Introductionmentioning
confidence: 99%